Evaluation of Factors Associated with Beliefs About Antidiabetic Medicine in Outpatients with Type 2 Diabetes at Hue University Hospital - Chuyen Le; Thi Minh Hoa Nguyen; Thi Kim Cuc Ngo; Thi Thuy Nhi Tran (Indonesian Journal of Pharmacy, 2023)
Poor adherence to antidiabetic medication, which causes diabetes-related complications and increases medical burden, has been an important concern for both patients and physicians. Enhancing patients' beliefs about medicine can partially improve their non-adherence status to medications. To evaluate the factors associated with beliefs about antidiabetic medicine in outpatients with type 2 diabetes at Hue University Hospital. A cross-sectional study was conducted on 396 outpatients diagnosed with type 2 diabetes mellitus at the Endocrinology Clinic at Hue University Hospital. We interviewed the patients using a questionnaire based on the Vietnamese version of the Beliefs about Medicines Questionnaire (BMQ-V). The study was conducted on 396 patients with type 2 diabetes, with a median age of 66.9 ± 13.7 years. The prevalence of outpatients achieving HbA1C and glycemic targets was 18.7% and 20.7%, respectively. According to the BMQ-V questionnaire, the participants’ beliefs about medicine had a mean score of 50.3 ± 8.1. The mean value of the Specific-Concerns subscale was the highest (14.5 ± 3.8) and the Specific-Necessity subscale was the lowest (9.8 ± 3.9). Multivariate regression analysis revealed a statistically significant association between BMQ score and HbA1c control status, duration of diabetes, and home blood glucose monitoring (p < 0.05). Coordination between clinical pharmacists and physicians should be strengthened to improve their positive beliefs and gradually reduce their negative beliefs about medicines, thereby increasing medication adherence and improving treatment effectiveness.